1993
DOI: 10.1093/ajcn/58.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of patterns of weight change in stage IV human immunodeficiency virus infection

Abstract: Weight loss is a major manifestation of infection with the human immunodeficiency virus (HIV). Prospective analysis of weight change was performed in 30 male subjects with stage IV HIV infection over a period of 9-49 mo and weight change events (> 4 kg) related to contemporaneous clinical events. Two distinct patterns of weight loss were observed: episodes of acute severe weight loss and episodes of chronic unremitting progressive weight loss. Thirty-three acute episodes (median 9.1 kg in 1.7 mo) and 23 chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(60 citation statements)
references
References 22 publications
3
54
1
1
Order By: Relevance
“…Em adultos infectados pelo HIV, o GER foi avaliado em diversos estudos 4,10,13,20,21 . Hommes et al, em 1991, encontraram um aumento de 8%, em relação a um grupo controle.…”
Section: Resultsunclassified
“…Em adultos infectados pelo HIV, o GER foi avaliado em diversos estudos 4,10,13,20,21 . Hommes et al, em 1991, encontraram um aumento de 8%, em relação a um grupo controle.…”
Section: Resultsunclassified
“…Malabsorption andaor altered metabolism probably also play an important role in the development or persistence of cachexia in AIDS. On the other hand, it was demonstrated that progressive wasting is not a constant phenomenon in AIDS patients and that the development of wasting is usually due to the presence of speci®c diseases, such as diarrhoeal disease (Macallan et al, 1993). Other opportunistic infections and fever may also lead to increased energy and protein needs (Eldridge, 1996), while HIV infection might exert a direct effect on energy balance that varies with the degree of immunosuppression (Sharpstone et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas acute weight loss in AIDS is more often associated with non gastrointestinal infections such pneumonia, opportunistic infection of the small intestine characteristically causes chronic disease with diarrhoea and malabsorption, and around 70% of chronic weight loss is associated with gastrointestinal infection and diarrhoea (Macallan et al 1993). Opportunistic parasitic gut infections cause severe diarrhoea and profoundly compromised small bowel absorptive function (Kapembwa et al 1990) and cause significant mortality in AIDS both in Western (Levine et al 1991) and developing countries (Gilks et al 1990).…”
Section: Hiv and The Gastrointestinal Tractmentioning
confidence: 99%